2018
DOI: 10.1016/j.ejor.2018.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the value of information sharing in two-stage supply chains

Abstract: There is a substantive amount of literature showing that demand information sharing can lead to considerable reduction of the bullwhip effect/inventory costs. The core argument/analysis underlying these results is that the downstream supply-chain member (the retailer) quickly adapts its inventory position to an updated end-customer demand forecast. However, in many real-life situations, retailers adapt slowly rather than quickly to changes in customer demand as they cannot be sure that any change is structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Our study is also related to the literature on information sharing in supply chain settings, such as one‐manufacturer‐one‐retailer (e.g.,Guo, ; Guo & Iyer, ; Mittendorf et al, ; Jiang et al, ; Huang & Wang, ; Teunter et al, ; Zhang et al, ), one‐manufacturer‐multiple‐retailers (e.g.,Li, ; Li & Zhang, ; Wu et al, ; Wang et al, ) and competing supply chains (Guo et al, ; Shamir & Shin, ; Ha et al, ; Guan et al, ; Wei et al, ). Some studies also investigate information sharing in a dual‐channel supply chain setting (Yue & Liu, ; Zhang et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our study is also related to the literature on information sharing in supply chain settings, such as one‐manufacturer‐one‐retailer (e.g.,Guo, ; Guo & Iyer, ; Mittendorf et al, ; Jiang et al, ; Huang & Wang, ; Teunter et al, ; Zhang et al, ), one‐manufacturer‐multiple‐retailers (e.g.,Li, ; Li & Zhang, ; Wu et al, ; Wang et al, ) and competing supply chains (Guo et al, ; Shamir & Shin, ; Ha et al, ; Guan et al, ; Wei et al, ). Some studies also investigate information sharing in a dual‐channel supply chain setting (Yue & Liu, ; Zhang et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The partnership between sellers and buyers is widely discussed in the first stream. For example, Cachon and Fisher [9], Lee et al [6], and Teunter et al [10] studied the value of information sharing between upstream and downstream firms. It is concluded that sharing information is beneficial to both parties only under certain conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, it is often hard and costly to obtain complete information on uncertain market for a manufacturer. Thus, production quantity is forecasted based on orders from the downstream retailer [6,10].…”
Section: Retailer's Behavior Undermentioning
confidence: 99%
See 1 more Smart Citation
“…Value of information (VoI) analyses have been developed and used specifically to assess the influence of uncertainty reduction (due to acquisition of new and improved information) on management decisions [3,4]. Similar to traditional sensitivity and uncertainty analysis, VoI analyses are concerned with the influence of uncertain parameters and model structures on model outcomes, but the focus is not on performance of individual model outputs, but rather on the change in ranking of management alternatives available to decision makers.…”
Section: Introductionmentioning
confidence: 99%